Living and studying at home : degrees of inequality - Riddell, Shelia; Tett, Lyn; Christie, Hazel; King, Rachael; Shan, Sofia (Emerald Publishing Limited, 2024)
Traditionally, the most socially and academically selective UK universities expected students to move from the family home to the institution during term time. More recently, there has been a growing trend for students to live at home and commute to university, with the proportion commuting driven in part by the COVID-19 pandemic and the cost-of-living crisis. Examining commuting through a social justice lens rather than focusing solely on the way in which commuters navigate home and university identities, Living and Studying at Home: Degrees of Inequality explores the social characteristics, experiences, and outcomes of commuting students in an old Scottish university, highlighting the social class dimension of commuting. To redress the social inequalities identified, the authors consider what universities can do to meet the needs of commuter students who are currently highly marginalised. Drawing on findings of recent research undertaken by the authors, chapters discuss why commuting is socially structured by a range of factors including social deprivation, caring responsibilities, ethnicity, disability, and being a mature student, and suggest future policy, cultural and pedagogical changes which challenge the systemic inequalities experienced by living at home students.
Keywords: Educational equalization -- Great Britain.; Minorities -- Education (Higher); Black people -- Great Britain -- Education (Higher); People with disabilities -- Great Britain -- Education (Higher); Cost and standard of living -- Great Britain.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books